1996
DOI: 10.1139/b96-124
|View full text |Cite
|
Sign up to set email alerts
|

Identification and microgeographic distribution of Mazzaella splendens and Mazzaella linearis (Gigartinaceae, Rhodophyta)

Abstract: Existing descriptions of the sister species Mazzaella splendens and Mazzaella linearis were insufficient to identify all low intertidal Mazzaella thalli along a wave exposure gradient in Barkley Sound, British Columbia. After sampling size classes of sporophytes and gametophytes, uni- and multi-variate analyses indicated that thalli at low and intermediate exposure sites were M. splendens, whereas thalli at the high exposure site were M. linearis. The longer and thicker stipe of M. linearis best distinguishes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Mazzaella splendens from sheltered habitats (figure 1a) can be discerned from wave-exposed populations of M. linearis (figure 1b), but a continuum of morphological intermediates (e.g. figure 1c) traverse the intervening wave-exposure gradient (Shaughnessy 1996). Mazzaella f laccida is also difficult to distinguish (compare figure 1d to e, f ) from M. splendens (Hommersand et al 1994) such that the 'Keys to the Benthic Marine Algae.of British Columbia.'…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mazzaella splendens from sheltered habitats (figure 1a) can be discerned from wave-exposed populations of M. linearis (figure 1b), but a continuum of morphological intermediates (e.g. figure 1c) traverse the intervening wave-exposure gradient (Shaughnessy 1996). Mazzaella f laccida is also difficult to distinguish (compare figure 1d to e, f ) from M. splendens (Hommersand et al 1994) such that the 'Keys to the Benthic Marine Algae.of British Columbia.'…”
Section: Resultsmentioning
confidence: 99%
“…Ross et al (2003) outlined possible scenarios to explain the apparent morphological continuum observed in the field for the M. linearis/splendens complex: (i) a single species exists with substantial morphological plasticity in response to wave exposure; (ii) two species exist, but one or both display phenotypic plasticity such that the intermediate plants are strictly of one species or the other, or a mixture of plants from both; (iii) the intermediate plants may be tetrasporophytes of M. splendens, which was reported to have a possible heteromorphic aspect to its alternation of generations ; (iv) the intermediates are hybrids between the two species; and (v) combinations of the previous could also explain these individuals. To evaluate the previous hypotheses, as well as the published ecological results (Shaughnessy 1996 figure 1c) had ITS sequence consistent with placement in M. splendens, a result which was consistent with a morphological reevaluation of the voucher (Ross et al 2003); and another that was identified as M. f laccida (figure 1d ), based on their interpretation of the identification keys in Gabrielson et al (2000), also proved to be M. splendens, leaving uncertainty as to whether or not M. f laccida extends into BC. The ITS was thus a powerful tool for resolving an outstanding species issue in the flora adjacent to the Bamfield Marine Station, but it had shortcomings.…”
Section: Resultsmentioning
confidence: 99%
“…M. splendens also does not have the developmental option of making its blade narrower like those of M. linearis in order to reach a length necessary for reproduction. Blades of M. splendens actually become wider when regrown at a high impact site with M. linearis (Shaughnessy 1994). Thus, the ability of M. linearis to produce longer, potentially reproductive blades within a high impact site is still greater than for M. splendens within this kind of site.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, M. linearis is only found in outer coast habitats subject to high wave impact and it has a longer, thicker stipe supporting the narrowest blade (Shaughnessy 1996). Differences in stipe and blade shape between M. linearis and the wide bladed form of M. splendens are not due to phenotypic plasticity, as they reproduce their original morphologies when regrown from holdfasts in reciprocal transplant sites (Shaughnessy 1994).…”
Section: Introductionmentioning
confidence: 98%
“…Relative to other species in the Gigartinaceae, M. splendens and M linearis are closely related because they have similar carposporangial anatomy (Kim 1976) as well as similar base sequences for the large subunit of the Rubisco gene (Hommersand et al 1994). The 2 species are distinguished by the depth of the tetrasporangial sorus in the blade (Kim 1976) and, in Barkley Sound, Canada, M. splendens has a short thin stipe with wide or intermediate-width blades whereas M. linearis has a long thick stipe and narrow blades (Shaughnessy 1996). A reciprocal common garden experiment where each species was regrown from holdfasts demonstrated that these vegetative differences were due to genetic differentiation rather than phenotypic plasticity (Shaughnessy 1994).…”
Section: Introductionmentioning
confidence: 99%